BROADBAND MICROWAVE MEASUREMENTS OF RELATIVE PERMITTIVITY AND PERMEABILITY OF MATERIALS - Rybin, Oleg; Abbas, Tahir (Journal of Research (Science), 2025)
measuring complex permittivity and permeability of materials at broadband microwave frequencies has been presented. Classification of type of the measurement methods to extract the complex permittivity and permeability of bulk materials has been done in this paper. Mathematical models of all the above-mentioned measurement types of methods are reviewed. Advantages and disadvantages of existing measurement devices/systems are described according to the classification made. A new design of test devices for the measurement system operating in broadband microwave frequency range has been proposed. Measurement system on the basis of the proposed device can be used for a measuring the ordinary bulk materials, ferrites (including fully magnetized) and magnetic materials but much cheaper then one to be made. The system is much cheaper than a free space measurement system. The approach to define the permeability tensor of magnetic materials using the test device is proposed as well.